2010
DOI: 10.1007/s11801-010-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Research on the flooding routing arithmetic of wireless sensor networks based on solar-blind UV light

Abstract: In this paper the solar-blind ultraviolet (UV) light is used as communication medium for wireless sensor networks (WSNs). Three types of single scattering UV communication models are introduced and a directional flooding model is proposed, which are based on the directionality of the UV communication and the traditional flooding routing model. The delay, delay jitter, throughput and energy consumption of the three types of communications of the new model are simulated and compared. The results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…If it was not, this indicated that CN t s had been allocated too many intracluster time slots. This action was penalized, with the corresponding probability being reduced according to (2). Then, CL polled the next cluster node CN t s + 1 from list L t , and the same polling process was repeated.…”
Section: Working Processmentioning
confidence: 99%
See 2 more Smart Citations
“…If it was not, this indicated that CN t s had been allocated too many intracluster time slots. This action was penalized, with the corresponding probability being reduced according to (2). Then, CL polled the next cluster node CN t s + 1 from list L t , and the same polling process was repeated.…”
Section: Working Processmentioning
confidence: 99%
“…Ultraviolet (UV) networks are mobile networks that use UV radiation as communication carriers to realize wireless multi-hop communication among UV communication terminals [1]. These networks can be applied to military networks, emergency services, disaster recovery, and other complex electromagnetic environments due to their excellent non-line-of-sight (NLOS) communication, high security, and all-weather operation [2]. The secure properties of UV networks include strong anti-interference abilities, good confidentiality, and low position resolutions [3]; thus, they have recently become a research hotspot [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In distributed estimation, each node in the network exchanges data with its neighbouring nodes as a local processing center to estimate some parameters of interest. Compared to centralised estimation in which a fusion center is needed for receiving and processing data from all agents in the network, distributed estimation reduces energy consumption, and is insensitive to the failure of the fusion center [1–3]. In terms of cooperation strategy among nodes in the network, distributed estimation algorithms are generally classified into the diffusion kind [4–15] and the incremental kind [16–18].…”
Section: Introductionmentioning
confidence: 99%